INTEGRASI STEAM DAN EDUCULTURE DALAM PELAKSANAAN KURIKULUM MERDEKA: SEBUAH STUDI TENTANG HAMBATAN DAN KEBUTUHAN GURU - Siti Raihan; Shasliani; Andi Makassau; Amir Pada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the internal barriers, external barriers, and needs of elementary school teachers in integrating STEAM (Science, Technology, Engineering, Arts, and Mathematics) and Educulture (culture-based education) in the implementation of the Merdeka Curriculum. The research employed a mixed-methods approach with an explanatory sequential design, involving 30 teachers and 5 principals from 7 elementary schools in Makassar City. Quantitative data were collected through a questionnaire measuring three dimensions (internal barriers, external barriers, and teacher needs), while qualitative data were obtained through semi-structured interviews with principals. The results showed that the highest internal barrier was teachers' lack of understanding of how to integrate STEAM with local wisdom (73%), while motivational aspects were at the lowest level (33%). The highest external barriers were the unavailability of integrated teaching module examples (87%), time constraints (83%), and the lack of practical training (80%). The most urgent teacher needs were integrated teaching module examples (48%) and practical training (30%). This study concludes that teachers are mentally ready but instrumentally unprepared, requiring interventions in the form of concrete examples, practice-based training, continuous mentoring, and strengthening cross-sector collaboration between education offices, universities, and local communities.